Astrocytes and Microglia Are Resistant to NAD+-Mediated Cell Death Along the ARTC2/P2X7 Axis - Rissiek, Björn; Stabernack, Joschi; Cordes, Maike; Duan, Yinghui; Behr, Sarah; Menzel, Stephan; Magnus, Tim; Koch-Nolte, Friedrich (Frontiers in Molecular Neuroscience, 2020)
ADP-ribosylation of the P2X7k splice variant on mouse T cells by ecto-ADP-ribosyltransferase ARTC2.2 in response to its substrate extracellular nicotinamide adenine dinucleotide (NAD+) triggers cell death. Since NAD+ is released as danger signal during tissue damage, this NAD+-induced cell death (NICD) may impact the survival of other cell populations co-expressing P2X7 and of one of the ARTC2 isoforms (ARTC2.1, ARTC2.2). NICD of brain-resident, non-T cell populations has only been rudimentarily investigated. In this study, we evaluated the susceptibility of two glia cell populations, astrocytes and microglia, towards NICD. We found that astrocytes and microglia strongly upregulate cell surface levels of ARTC2.1 and ADP-ribosylation of cell surface proteins in response to treatment with lipopolysaccharide (LPS) and the mitogen-activated protein kinase kinase (MEK) 1 and 2 inhibitor U0126, but do not respond to extracellular NAD+ with P2X7 activation and induction of cell death. Furthermore, we found that astrocytes and microglia preferentially express the ADP-ribosylation-insensitive P2X7a splice variant, likely accounting for the resistance of these cells to NICD.